PROSES PEMBENTUKAN KOMUNITAS MUSLIM INDONESIA - AM, Mirhan (Jurnal Studia Insania, 2014)
This paper is a study in mapping out more about the process of formation of the Muslim community in Indonesia. History is a reconstruct of the past. It seems as if the past was to be away from the present. Is it true that this view. We borrow the Kuntowijoyo?s words: ?Historians are like people take who takes the train to look back, and he can freely turn to the right and to the left, which can not be done is to look ahead?. History is a valuable clue, a picture of the past that can be used as guidelines in stride, present and future. The Indonesian Islam history has significance for this nation generation. Because it has its own characteristics compared to the history of Islam in other countries. It can give the feel of the real Islam in Indonesia. The Indonesian Islam is an Islamic hue promising future in the era of globalization. Thus, Indonesian Islam will be in focus in the eyes of the world. In this description, the writer describes the entry and the development of Islam in Indonesia with discussion; process and the introduction of Islam to Indonesia, acceptance by indigenous and institutionalization of Islam in society. Then, point the establishment of Islam in Indonesia, as well as the transformation of Indonesia society